A One-stage Factor VIII (Antihaemophilic Globulin) Assay and its Use on Venous and Capillary Plasma - Hardisty, R. M; Macpherson, Janet C.; Note on the Calculation of Confidence Limits by G. I. C. Ingram (Thrombosis and Haemostasis, 1962)
A one-stage factor-VIII assay is described, based on the method of Lang-dell, Wagner and Brinkhous (1953), in which contact activation is controlled by the addition of a suspension of kaolin to the system. Experiments to show the effect of this modification on the clotting times and reproducibility of the system are presented.The error of the method is expressed in terms of the confidence limits of a random series of field assays, which lay between 64—156% and 76—131% of the observed result.The normal range of factor-VIII concentrations, as determined by this method on venous plasma samples from 116 normal subjects, was 50—170%, with a roughly normal distribution. There was good correlation between the results of one-stage and two-stage factor-VIII assays carried out in parallel on 110 plasma samples and between the observed and expected factor-VIII concentrations of a series of mixtures of normal and haemophilic plasma.The use of the assay on capillary plasma samples is described, and the results compared with those obtained on venous plasma. The practical value of capillary factor-VIII assays is discussed.